Synchrotron radiation and its polarization from runaway electrons in toroidal magnetic fields - Sobolev, Ya.M. (Вопросы атомной науки и техники, 2015)
The formulas to describe synchrotron radiation and its polarization in toroidal magnetic field configurations are presented. The radiated power and direction of polarization of the synchrotron radiation spot of runaway electrons for medium-sized tokamaks are estimated. Two polarization models are proposed. It is shown that the polarization measurements give additional diagnostics for the radiating relativistic electrons.